Racismo e Saúde Mental de meninas negras em contexto escolar - Amaral, Raisa Carolina Carvalho (2026)
This dissertation presents an intervention-research conducted with Black girls from lower secondary and upper secondary education in public schools in the municipality of Sorocaba, São Paulo, Brazil, focusing on the relationship between racism and mental health in the school context. The study was funded by the Coordination for the Improvement of Higher Education Personnel (CAPES). The research emerges from the listening practices and life trajectory of a Black woman affected by structural racism, who understands listening and care as practices of resistance. The objective was to understand how racism affects the mental health of Black girls in the school environment, as well as to promote spaces for identity strengthening, active listening, and collective confrontation of racial violence. Cartography was adopted as the methodological approach, understood as a way of accompanying processes and subjective movements produced throughout the intervention. Conversation circles were conducted with Black girls aged 11 to 16, addressing themes related to race, gender, identity, and mental health. The results indicate that collective encounters fostered practices of care, support, and resistance, contributing to the emotional, social, and identity strengthening of the participants. The study highlights the importance of permanent and intersectional strategies that promote autonomy, a sense of belonging, and the confrontation of racism in everyday school life, contributing to the construction of an anti-racist education committed to the urgent realities of Black girls’ lives.